(untitled) (International Journal of Current Engineering and Technology, 2014)
This paper reviews the most experimental works on anchorages by hooked and bent bars in reinforced structure. Some of these works resulted in forming expressions to design bond strength by codes of practice like ACI. None of these works represent the real structure conditions as they were carried out on pull-out specimens except those unpublished tests by Gulparvar which applies directly to anchorages at simple supported beams. There is Schiessl’s theoretical approach to treat and calculate anchorage resistance based on the of the compatibility of deformations between straight lead lengths and terminal bends and hooks.This review has been done as a part of a research study and used as a base to undertake a substantial test program on end anchorage at simply supported beams at London South Bank University between 2003- 2005 by the author of this paper to obtain PhD in structural engineering. The present situation seems to be that there are 5 results by Gulparvar available from tests to failure of  90 bends at supports and none for  180 bends. There are probably isolated results from tests in which unintended anchorage failures have occurred, but the total of information is clearly very small.